Preparation of Anti-reflective Coatings on Solar Glass - Wang, Jing; Zhang, Jin; Liu, Zhenying (Asian Journal of Chemistry, 2013)
Anti-reflective coatings have been applied on solar glass, which can increase the transmittance by 5 % or more and efficiently improve the conversion efficiency of solar cells. In this paper, there are three kinds of antireflective coatings i.e., SiO2 antireflective coatings, TiO2 anti-reflective coatings and SiO2/TiO2 double-layer antireflective coatings by dipping slide glasses in the sols and being compared the three kinds of transmittance variation when they are prepared in different drawing speed.